Outcomes and complications among nonagenarians undergoing cardiac surgery: A scoping review - Laurence Weinberg; Jarryd Ludski; Bradly Carp; Je Min Suh; Anoop N. Koshy; Cilla Haywood; Benjamin Churilov; Dong-Kyu Lee; Michael Yii (PLoS ONE, 2025)
Introduction This review was aimed at understanding the scope of evidence regarding outcomes and complications in nonagenarians (90–99 years of age) undergoing open cardiac surgery. Methods The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Extension for Scoping Review Protocol guidelines. A search of three databases, MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials, identified articles pertaining to nonagenarians undergoing various open cardiac surgical procedures. No restrictions were applied to study design or publication date. Results From the initial 1826 articles identified, we included 28 studies from eight countries in a total of 6411 nonagenarians. The median 30-day mortality rate was 10.5% (IQR 7.2–14.6). Postoperative complication rates were reported in 20 studies (71%), and the median major complication rate was 71.4%. Respiratory, cardiac, renal, neurologic, gastrointestinal, and/or infectious complications were reported in 19%, 20%, 14%, 18%, 5%, and 9% of cases, respectively. The median length of hospital stay was 12.5 days (IQR 10.4–18.0). No studies reported unplanned readmissions to the intensive care unit or detailed patient-centered outcome measures. Conclusions Although age alone should not preclude nonagenarians from undergoing cardiac surgery, the procedure is associated with a significantly elevated risk of morbidity and a relatively high mortality rate. The review findings emphasize the need for international registry data to identify risk factors associated with adverse outcomes, explore strategies to decrease the risk of major complications, and improve postoperative quality of life. Moreover, creating and implementing uniform preoperative frailty assessments, and correlating them with surgical outcomes, will be crucial. Developing standardized patient-reported experience and outcome measures will also be imperative. Scoping review registered on OSF registries (https://osf.io/4mg7n).